The clinical significance of in-house metagenomic next-generation sequencing for bronchoalveolar lavage fluid diagnostics in patients with lower respiratory tract infections - Li, Shixiao; Qin, Jiajia; Zhou, Peng; Peng, Minfei; Qian, Jiao; Cai, Yingying; Shi, Qingxin; Tung, Tao-Hsin; Shen, Bo; Yu, Sufei (Frontiers in Cellular and Infection Microbiology, 2022)
Objective: Metagenomic next-generation sequencing technology (mNGS) has the potential to detect a wide range of pathogenic microorganisms. However, reports on different platforms of mNGS in patients with lower respiratory tract infections applied to bronchoalveolar lavage fluid (BALF) remain scarce. Methods: 306 patients with suspected lower respiratory tract infection were enrolled from January 2019 to December 2021. Both conventional methods and mNGS of BALF were analyzed retrospectively. BALF mNGS were performed by commercial and in-house laboratory, respectively. The diagnostic value of pathogens and the clinical implications were compared between different groups. Results: The positive rate of mNGS was 85.26% in the in-house group and 70.67% in the commercial group. mNGS significantly increased the pathogen detection rate, compared with conventional methods. Pathogens detected by mNGS were composed of bacteria, fungi, viruses, and special pathogens. And the in-house platform performed well on wider spectrum of microbial distribution. Furthermore, in-house platform had an advantage in presenting multimicrobial ecosystem in patients with different underlying diseases. Among the mNGS-positive cases, 34 (32.0%) cases adjusted antibiotics in the commercial group, and mNGS led to a change of treatment in 51 (38.3%) cases in the in-house group. Furthermore, the turnaround time of mNGS and the time from mNGS to discharge in the in-house group were significantly shorter than that in the commercial group. Conclusion: In-house mNGS can show a higher detection rate and a wider spectrum of pathogens, with potential benefits for the clinic.